2010
DOI: 10.1007/s10549-010-0766-6
|View full text |Cite
|
Sign up to set email alerts
|

TGFB1 T29C polymorphism and breast cancer risk: a meta-analysis based on 10,417 cases and 11,455 controls

Abstract: Breast cancer is the most prevalent cancer worldwide. Many published articles have evaluated the association between the transforming growth factor beta 1 (TGFB1) T29C polymorphism and breast cancer risk. However, the results remain inconclusive. In order to derive a more precise estimation of the association, a meta-analysis was performed in this study. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association. A total of 12 studies including 10,417 breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…With respect to C-509T polymorphism, Fang found an association with colorectal cancer in an Asian population, 25 while previous three meta-analyses had confirmed that it was not associated with a risk of breast cancer. [26][27][28] With respect to T869C polymorphism, four meta-analyses had confirmed that it was not associated with a risk of breast cancer, [29][30][31][32] but some studies concluded an association with breast cancer. 28,33 However, Wei suggested that T869C polymorphism had no association with gastric, liver and lung cancer, but an association with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to C-509T polymorphism, Fang found an association with colorectal cancer in an Asian population, 25 while previous three meta-analyses had confirmed that it was not associated with a risk of breast cancer. [26][27][28] With respect to T869C polymorphism, four meta-analyses had confirmed that it was not associated with a risk of breast cancer, [29][30][31][32] but some studies concluded an association with breast cancer. 28,33 However, Wei suggested that T869C polymorphism had no association with gastric, liver and lung cancer, but an association with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also emphasized that the CC genotype was protective against tumour development (Sparks et al ., ). Various studies have further revealed that there is no apparent relationship between TGF‐β1 T869C polymorphism and tumour risk (Jin et al ., ; Meyer et al ., ; Gu et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Other authors have also emphasized that the CC genotype was protective against tumour development (Sparks et al, 2004). Various studies have further revealed that there is no apparent relationship between TGF-b1 T869C polymorphism and tumour risk (Jin et al, 2008;Meyer et al, 2009;Gu et al, 2010). Li et al (2004) evaluated the prevalence of the TGF-b1 T869C polymorphism in 351 patients with prostate cancer and 303 male controls and observed significant differences in the CC versus TC and TT genotype distribution with a 1.62-fold increased risk of prostate cancer (95% CI, 1.14-2.30; P = 0.007) for men with the TC or TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all five meta-analyses were published in the same year [29], [42], [51], [52], [53]. Two of these meta-analysis stated no association between c.29C>T polymorphism and breast cancer [29], [51], while the two others stated no overall association between this substitution and breast cancer risk, but an increased risk of breast cancer with 10P allele in Caucasians [42], [52], and yet another meta-analysis stated significant association of 10P in overall analysis as well as in the Caucasian group [53]. Contrary to the observations of all these meta-analyses, particularly the latter three, we found the alternate allele (‘T’ or ‘leucine’) to be a risk factor for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TGF β are known as low penetrance genes in cancer [29]. There are three isoforms of TGF-β (TGF-β1, TGF-β2, and TGF-β3), of which TGF- β1 is most widely expressed [30].…”
Section: Introductionmentioning
confidence: 99%